History and Current State of Forensic Analysis of Extremist Materials - M. V. Kroz; N. A. Ratinova (Теория и практика судебной экспертизы, 2016)
The paper looks at the history and current state of forensic analysis of the content and intentionality of contentious (extremist) materials. It discusses different approaches based in linguistics, psychology, and social sciences/humanities, as well as issues relating to integrated forensic psycholinguistic analysis. Techniques and methodological recommendations described in the paper were developed by the experts of the Research Institute for Law and Order of the Prosecutor General's Office of the Russian Federation, various national forensic organizations, such as the Russian Federal Center of Forensic Science of the Ministry of Justice of the Russian Federation, the Forensic Science Center of the Ministry of Internal Affairs of the Russian Federation, forensic divisions of the Federal Security Service of the Russian Federation, and members of the scientific community. Generic methodologies (linguistic and psycholinguistic) proposed by government agency specialists for the forensic evaluation of extremism manifestations are discussed, including the level of methodological sophistication, and the problem of methodological harmonization in this field of forensics.